Immediate Postpartum Long-Acting Reversible Contraception: A Comparison Across Six Humanitarian Country Contexts - Gallagher, Meghan C.; Morris, Catherine N.; Fatima, Aisha; Daniel, Rebekah W.; Shire, Abdikani Hirsi; Sangwa, Bibiche Malilo Matala (Frontiers in Global Women's Health, 2021)
Postpartum family planning (FP) could prevent more than 30% of maternal deaths by effectively spacing births; this is particularly relevant in humanitarian contexts given that disproportionate maternal death occurs in countries affected by crises. In humanitarian settings, where accessing functional facilities is challenging with security risks that constrain movement, many women are unable to return for their 6-week postpartum visits and thus unable to receive FP counseling and adopt a method that suits their fertility intentions. Thus, immediate postpartum family planning (IPPFP) interventions, focused on long-acting reversible contraception (LARC) and tailored toward humanitarian contexts, could contribute to healthy timing and spacing of pregnancy, particularly among postpartum women, and improve maternal and newborn health. In 2014, Save the Children integrated postpartum intrauterine device (IUD) services into its FP package in emergency settings. In 2017, this expanded to include postpartum implant uptake as well, given updated World Health Organization guidelines. Three countries (Democratic Republic of Congo, Somalia, and Pakistan) opted for higher-intensity programming for IPPFP with a specific focus on LARC. This involved training delivery-room providers on counseling and provision of IPPFP, as well as training antenatal care nurses in counseling pregnant women on IPPFP options. Three countries (Rwanda, Syria, and Yemen) did not implement notable IPPFP interventions, although they provided the standard of care and monitored provision via monthly service delivery data. Using data from 2016 to 2019, we examined trends in immediate postpartum LARC (IPP LARC) uptake and compared countries with higher-intensity IPP LARC interventions to countries providing standard care. Tests of association were performed to assess the significance of these differences. In the country programs with higher-intensity IPPFP interventions, IPP LARC as a percentage of all deliveries was much higher overall during the July 2016–December 2019 period. The IPP LARC intervention had a significant impact on the overall proportion of women and girls who adopted an IUD or implant within the first 48 h of delivery, F(1, 250) = 523.16, p < 0.001. The mean percentage of IPP LARC among all deliveries in intervention country programs was 10.01% as compared to 0.77% in countries providing standard care. Results suggest that there is demand for IPP LARC in humanitarian contexts and that uptake increases when multipronged solutions focusing on provider training, community outreach, and service integration are applied.